The Effect of Sodium Bicarbonate towards the Growth Performance and Biomass Production of Microalgae - Tan, Wei Yein (Universiti Teknologi PETRONAS, 2016)
Recently, as dwindling fossil fuel reserves and growing concerns about global warming, biodiesel has gained immense popularity because it is renewable and environmental friendly. Nonetheless, the microalgae biodiesel has attracted increasing attention as biodiesel production due to its higher growth rate and CO2 bio-fixation rate. This research project was conducted on Chlorella vulgaris to check on the effect of sodium bicarbonate on the performance growth and biomass production of microalgae. The growth behavior of Chlorella vulgaris will be studied under different concentration of sodium bicarbonate. Compost will be used as the main nutrient source for the microalgae cultivation. Besides, the effect of cultivation parameters such as pH value and amount of nutrient towards the growth of microalgae also will be studied in this project. The growth of microalgae will be measured by using spectrophotometer. After the microalgae have reached stationary phase, the microalgae will be dried and its biomass will be collected.